2008
DOI: 10.1080/10915810802514476
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Toxicological Potential of Capsinoids: X. Safety Assessment and Pharmacokinetics of Capsinoids in Healthy Male Volunteers after a Single Oral Ingestion of CH-19 Sweet Extract

Abstract: The safety and pharmacokinetics of capsinoids, physiologically active ingredients of CH-19 Sweet extract, were investigated in 16 healthy male volunteers following a single oral ingestion of CH-19 Sweet extract. The study subjects consumed soft gel capsules containing either capsinoids (15 or 30 mg/person) or placebo. Capsinoids were well tolerated, and no clinically significant changes in physical examinations, blood pressure, heart rate, body temperature, electrocardiogram, hematology, blood chemistry, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…After 90 min, capsaicin could not be detected (Chaiyasit et al, 2009). These results suggest that Bernard et al (2008) were unable to create a pharmacokinetic profile of capsaicinoids after administration of 15 and 30 mg of capsaicin /person, because they used a lower detection limit of 10 ng/ml. Oral capsaicin has more relevance to molecular gastronomy than to any therapeutic options.…”
Section: A Oral Administrationmentioning
confidence: 81%
“…After 90 min, capsaicin could not be detected (Chaiyasit et al, 2009). These results suggest that Bernard et al (2008) were unable to create a pharmacokinetic profile of capsaicinoids after administration of 15 and 30 mg of capsaicin /person, because they used a lower detection limit of 10 ng/ml. Oral capsaicin has more relevance to molecular gastronomy than to any therapeutic options.…”
Section: A Oral Administrationmentioning
confidence: 81%
“…2 Similarly, a study in human volunteers reported that following an ingestion of up to 30 mg/kg capsinoid, neither capsinoids nor VOH was detectable in the plasma. 13 These results suggest that almost all, if not all, of the administered capsinoids were metabolized either in Each value represents mean + standard deviation of 3 individuals. Where the concentration of 2 or 3 of 3 cases was below the limit of quantitation (20 Zg/mL), the result is expressed as ND (not determined).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, intact capsinoids have not been detected in the circulating blood of humans after their oral intake (30 mg/person). 38) We next revealed that the capsinoid-induced thermogenesis was abolished by denervation of the extrinsic nerves in the jejunum. Since capsinoids are thought not to pass through the gastrointestinal wall and TRPV1 is expressed in the extrinsic nerves of the jejunum, 22) capsinoids are thought to enhance thermogenesis via TRPV1 expressed in these extrinsic nerves.…”
Section: Discussionmentioning
confidence: 99%